PERANCANGAN ULANG TATA LETAK FASILITAS PRODUKSI PABRIK TAHU SRIKANDI JUNOK BANGKALAN - Muh Faishol; Sri Hastuti; Millatul Ulya (AGROINTEK, 2013)
Industrial problems not only in how much investment should be planted, production and marketing procedures but requires planning production facilities covering the location of facilities planning and design of facilities. Facility design is important to get the best layout in the transport of materials so that the production process takes place quickly. This study aimed to redesign the layout of factory production facilities from the Srikandi’s Tofu industry at the district of Bangkalan to be more effective. This design based on the connectivity of production process flow and the distance of material removal. The method used in this study is Blocplan method. Best layout results using Blocplan produce 1.00 layout score and 5-6 distance proximity to the exchange boiler room and the room soaking